Influence of carbon type on carbon isotopic composition of coal from the perspective of solid-state 13C NMR. (1st June 2019) - Ding, Dianshi; Liu, Guijian; Fu, Biao
Highlights: δ 13 C values between −22.9‰ and −25.1‰ were measured for 12 Chinese bituminous coals. 13 C was enriched in the coals with more aromatic carbons. The aromatic C/aliphatic C ratio may influence the δ 13 C value of bituminous coal. Abstract: A total of twelve coal samples at bituminous rank from China were studied using a combination of elemental analyzer/isotope ratio mass spectrometry (EA/IRMS) and solid-state 13 C nuclear magnetic resonance (NMR) spectroscopy techniques to determine their carbon isotopic compositions and carbon types. Carbon isotope analysis showed that the δ 13 C values of the studied coals ranged from −22.9‰ to −25.1‰ and correlated significantly with the ratios of aromatic carbons to aliphatic carbons. The studied coals were enriched in 13 C due to the fact that the amount of 13 C-enriched aromatic carbons is more than that of 13 C-depleted aliphatic carbons. The observations suggest that carbon isotopic compositions of whole coal may be controlled by the distribution of carbon types.